Magnesium...the Metal of Motion - Dow Chemical Company (1944)
Print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. The advertisement features illustrated depictions of Dowmetal in use in the materials-handling and industrial equipment industries, with accompanying text detailing Dowmetal's lightness and durability relative to other structural metals. This advertisement appeared on page 45 of a 1944 edition of Newsweek.
Keywords: Dow Chemical Company; Corporations; Chemical industry; Magnesium; Magnesium alloys; Magnesium industry and trade; Advertising; Advertising, Industrial